FAKTOR-FAKTOR RISIKO FISKAL DALAM PENGANGGARAN DAERAH (Studi pada Pemerintahan Aceh) - Jalaluddin - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2010)
This research was conducted with the objective of identifying risk actors in fiscal budgeting of the Government of Aceh. Theoretically, the results of this study are expected to provide inputs for the Government of Aceh to be able to do things that help to reduce fiscal risks in the Aceh government budgeting. The data used were obtained through field research through the deployment of a questionnaire to measure attitudes, opinions, and perceptions of a person or group of persons of a particular social phenomenon, which has been specifically defined by the researchers. The population in this study was all officials involved in financial processes, both constituting (SKPA) and the budget approval board (DPRA). The test results produced 11 (eleven) factor reduced from 32 items and has a value of variable loading â‰¥ 0.5 which consists of four sources of risk of regulatory factors and mechanisms in the budgeting area, namely: with KUA and budget documents synchronization factors, factors of risk management in government area, changes in regulatory systems of budgeting and fiscal stress associated with the consideration of budget surpluses and deficits; three sources of risk from political factors in the budgeting area, there are: superiority of power factor (discretionary power) and the opportunistic behavior of individual legislators as well as factors executive and legislative relations (related mechanism formulation and discussion of budget); and four sources of risk factors of opportunistic behavior and moral hazard in budgeting, consisted of opportunistic behavior of individual in formulating the budget, a factor of moral hazard and the proposed budget planners, management public organizations factor related to clarity of responsibility, authority and functions as well as the potential for fraud in the budgeting process.Â Keywords: factors, regulation and mechanisms, politics, opportunistic behavior, moral hazard, budgeting